Forecasting the Consumer Price Index in Banyumas Regency Using Double Exponential Smoothing with Proportional Integral Derivative Controller - Ashar, Nurcahya Yulian; Abiyyin, Maulana Fatih (Universitas Airlangga, 2025)
The Consumer Price Index (CPI) is a crucial measure of inflation and the cost of living within a specific region. Accurate CPI forecasts are essential for policymakers, businesses, and stakeholders to make informed decisions. This study utilizes the Double Exponential Smoothing (DES) method to forecast the CPI for Banyumas Regency in January 2025, employing monthly CPI data from January 2020 to December 2024. The DES method was selected due to the observed upward trend in historical CPI data. Python programming was employed to optimize the smoothing parameters α and β, and the results were evaluated using Mean Absolute Deviation (MAD), Mean Squared Error (MSE), and Mean Absolute Percentage Error (MAPE). The forecasted CPI for January 2025 is 106.36, with high accuracy indicators, including a MAPE of 0.26%, demonstrating that DES is a reliable model for CPI forecasting in Banyumas Regency.